Proton T(2) Measurement and Quantification of Lactate in Brain Tumors by MRS at 3T In Vivo - Madan, Akshay (Magn Reson Med, 2014)
PURPOSE: To evaluate the T(2) relaxation time of lactate (Lac) in brain tumors and the correlation of the T(2) and concentration with tumor grades. METHODS: Eight pairs of the subecho time sets of point-resolved spectroscopy were selected between 58 and 268 ms, with numerical and phantom analyses, for Lac T(2) measurement. In-vivo spectra were acquired from 24 subjects with gliomas (13 low grade and 11 high grade) and analyzed with LCModel using numerically-calculated basis spectra. The metabolite T(2) relaxation time was obtained from monoexponential fitting of the multi-TE signal estimates versus TE. The metabolite concentration was estimated from the zero-TE extrapolation of the T(2) fits. RESULTS: The Lac T(2) was estimated to be approximately 240 ms, without a significant difference between low and high grade tumors. The Lac concentration was estimated to be 4.1±3.4 and 7.0±4.7 mM for low and high grades respectively, but the difference was not significant. CONCLUSION: The Lac T(2) was similar among gliomas regardless of their tumor grades. This suggests that the T(2) value from this study may be applicable to obtain the T(2) relaxation-free estimates of Lac in a subset of brain tumors.